Firewall Analytics in DNS and SYN Flood Protection on Mikrotik CCR in the North Aceh District Government - Nanda Imanda; Dahlan Abdullah; Fajriana Fajriana; Nurdin Nurdin; Munirul Ula (Malikussaleh University, Aceh, Indonesia, 2025)
This study investigates the implementation of an analytical firewall on the Mikrotik Cloud Core Router (CCR) device for network protection against Domain Name System (DNS) and Synchronise Flood (SYN Flood attacks in the information technology infrastructure of the North Aceh Regency Government. DNS-based attacks and SYN Flood have demonstrated a significant disruptive capacity for the continuity of electronic public services, illustrating the urgency of robust security protocols on government infrastructure. The study implemented a quantitative-experimental approach, with methodological triangulation in empirical data acquisition through controlled attack simulations, firewall log analysis, and semi-structured interviews with technical personnel. Experiments are designed with variations in attack intensity to evaluate system resilience thresholds, while firewall log analysis facilitates the identification of anomalous patterns through detection algorithms. The analytics process applies parametric evaluation to temporal mitigation metrics, packet processing capacity, and operational implications on network performance, complemented by descriptive statistical analysis that explores data distribution and temporal trends. The results indicate the differential effectiveness of the specific firewall configuration against a specific attack typology, with an empirical determination of optimisation parameters for real-time mitigation. This research contributes to the corpus of knowledge regarding the security of government networks through the derivation of protective models that are adaptive to the operational characteristics of public infrastructure. The findings have substantive implications for cybersecurity policy formulation in the administrative context of local governments, with extensive significance for the implementation of network architectures that are resilient to volumetric attacks and protocol exploitation.